Práticas de ampliação do tempo escolar: uma proposta de educação em tempo integral na contemporaneidade - Pinto, Natasha Souto Franca (2018)
The present study discusses the performance of educational policies, regarding the practice of expanding school time in the contemporary scenario as being fundamental to meet the demands of society with regard to social, cultural and economic problems. This discussion takes place on the projection of problems within the school, which, as an institution of the State, has as its function the educational development of the population of children, young people and adults, who, due to the emptiness of the State, constitute a risk to the society. In this context, it is important to think and understand the productivity of full-time education in today's society and therefore, the research begins with material analyzes for this understanding. After selecting the analytical materiality, it was proposed to analyze the emergence of policies to extend school time in Brazil, to delineate the grade of intelligibility and own knowledge to full-time education; to problematize the discursive field of practices of school time extension identified in the documents and materials of analysis; and indicate a possible proposal for full-time education in Early Childhood Education of the Baptist School. Full-time education constitutes a strategy of government produced for the population, in view of the protagonism that the school institution starts to constitute in a neoliberal logic. In this bias, the research addressed the administration of time in integral education, which articulated to a powerful instrument of social control and mobilizes mechanisms that regulate the conduct of individuals. Considering the problematizations made by the research, it was possible to develop as a product of the study a proposal of full-time education for the Early Childhood Education of the Baptist School that, from 2017 onwards, instituted the coordination of the Project of Integral Education in Early Childhood Education. Based on this proposed product and its implementation, it is intended a process of reflection at the locus of practices to increase schooling time with the objective that the full time of the students in the school, be produced by new ways of conducting the students and by new configurations for the teaching and learning process.